Counseling and psychotherapy theories in context and practice skills, strategies, and techniques - Sommers-Flanagan, John 1957-; Sommers-Flanagan, Rita 1953- (John Wiley and Sons, Inc., 2015)
"Student-friendly and comprehensive, Counseling and Psychotherapy Theories in Context and Practice, Second Edition provides an in-depth understanding of the origins, development, and key figures of each major theory and strongly emphasizes the application of these theories in real-world practice. Pedagogical features include opening chapter outlines, "Putting It In Practice" boxes, practitioner reflections, ethical highlights, case examples, as well as chapter summaries, chapter glossaries, and recommended readings and resources. The Second Edition includes a new section on treatment planning in each chapter and increased coverage of multicultural issues. A Study Guide for students is also available (978-0-470-90437-4)"--Provided by publisher.